2023
DOI: 10.3389/fimmu.2023.1302702
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio as a predictor of poor outcomes of Mycoplasma pneumoniae pneumonia

Dan Li,
Haiyan Gu,
Lei Chen
et al.

Abstract: IntroductionMycoplasma pneumoniae pneumonia (MPP) may lead to various significant outcomes, such as necrotizing pneumonia(NP) and refractory MPP (RMPP). We investigated the potential of the peripheral blood neutrophil-to-lymphocyte ratio (NLR) to predict outcomes in patients with MPP.Methods and materialsThis was a prospective study of patients with MPP who were admitted to our hospital from 2019 to 2021. Demographic and clinical data were collected from patient records and associated with the development of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Additionally, the caseonecrosis noted in the lungs and tonsils of bison in this study was characteristic of the clinical presentation noted in naturally occurring M. bovis infection of bison ( 11 , 12 , 32 ) and experimentally infected cattle ( 27 , 30 ). The elevated blood neutrophil counts observed in bison exhibiting severe disease is an interesting finding that has been previously shown to be associated with poor outcomes of pneumonia in humans and enhanced disease in mice with Mycoplasma pneumoniae ( 33 , 34 ), though has never been reported during M. bovis infection. Together these findings suggest that BHV-1, M. bovis coinfection can recapitulate the pathology observed in naturally infected bison which is similar to that observed in cattle.…”
Section: Discussionmentioning
confidence: 80%
“…Additionally, the caseonecrosis noted in the lungs and tonsils of bison in this study was characteristic of the clinical presentation noted in naturally occurring M. bovis infection of bison ( 11 , 12 , 32 ) and experimentally infected cattle ( 27 , 30 ). The elevated blood neutrophil counts observed in bison exhibiting severe disease is an interesting finding that has been previously shown to be associated with poor outcomes of pneumonia in humans and enhanced disease in mice with Mycoplasma pneumoniae ( 33 , 34 ), though has never been reported during M. bovis infection. Together these findings suggest that BHV-1, M. bovis coinfection can recapitulate the pathology observed in naturally infected bison which is similar to that observed in cattle.…”
Section: Discussionmentioning
confidence: 80%
“…The NLR is often relied on as a valuable tool to predict the prognosis of infectious diseases through monitoring systemic inflammation in children 22 . High levels of NLR are strongly linked to negative outcomes, so it is advisable to consider NLR as an unfavorable prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…Mycoplasma pneumoniae (MP) is a common pathogen that causes lower respiratory tract infections in children 1 and cause up to 20 to 40% of community-acquired pneumonia 2 . In China, Mycoplasma pneumoniae pneumonia (MPP) accounts for about 32.4% of community-acquired pneumonia in children 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Dan and colleagues investigated the potential of the peripheral blood neutrophil-to-lymphocyte ratio (NLR) to predict outcomes in patients with MPP. They found that Patients with a high NLR were more likely to develop NP and refractory Mycoplasma pneumoniae pneumonia (RMPP) and require intensive care, and had longer total fever duration, longer hospital stays, and higher hospitalization expenses than those with a low NLR 1 . The results suggested that the NLR can serve as a predictor of poor prognosis in patients with MPP and can predict the occurrence of NP, RMPP, and other poor outcomes.…”
Section: Introductionmentioning
confidence: 99%